Embryonic timing, axial stem cells, chromatin dynamics, and the Hox clock - Deschamps, Jacqueline; Duboule, Denis (Cold Spring Harbor Laboratory Press, 2017)
Collinear regulation of Hox genes in space and time has been an outstanding question ever since the initial work of Ed Lewis in 1978. Here we discuss recent advances in our understanding of this phenomenon in relation to novel concepts associated with large-scale regulation and chromatin structure during the development of both axial and limb patterns. We further discuss how this sequential transcriptional activation marks embryonic stemcell-like axial progenitors in mammals and, consequently, how a temporal genetic system is further translated into spatial coordinates via the fate of these progenitors. In this context, we argue the benefit and necessity of implementing this unique mechanism as well as the difficulty in evolving an alternative strategy to deliver this critical positional information.
Keywords: Chromatin; Collinearity; Embryos; Hox genes; Stem cells; TAD; Transcription; Genetics; Developmental Biology; Journal Article; Review